PARTISIPASI ORANG MUDA KATOLIK DALAM PELAYANAN MISDINAR DI PAROKI ST. MONTFORT SERAWAI - Andreas Christo Paulus Daniel; Antonius Denny Firmanto (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2023)
Catholic Youth Participation in acolyte care St. Montfort Serawai. The problem in this research was the level of involvement of young Catholics in parish pastoralism. It turned out that the young Catholics in this parish are sometimes only semi-active in parish acolyte care. The purpose of this study was to identify the factors that cause young Catholics to be semi- active in parish pastoral care so that this problem can be addressed properly. This study used a qualitative research method, with a questionnaire via google form to young Catholics in Parrish St. Montfort Serawai. This questionnaire allows the author to assess the situation of young Catholics in pastoral life in the parish. There were 43 people who answered the questionnaire. The data were processed by categorizing and organizing them so that it can provide research results based on the data. Based on the findings of this study, young Catholics began to be actively involved in pastoral life in Parish St. Montfort Serawai.